Bio-waste derived self-templated, nitrogen self-doped porous carbon for supercapacitors. (September 2022) - Nanda, Om Priya; Das, Nishat Kumar; Sekar, Prasanna; Ramadoss, Ananthakumar; Saravanakumar, Balasubramaniam
Abstract: The preparation of low-cost and scalable, porous activated carbon received great interest because of the huge need for electrode materials for supercapacitor applications. In this work, the porous activated carbon is prepared from shrimp shell waste by a two-step process; i.e. carbonization and KOH activation process. Moreover, the presence of inherent CaCO3 acted as a self-template to make the additional porous structure. The prepared activated carbon has been verified through various physical and chemical characterizations. The results confirm the prepared activated carbon flakes possess numerous macro and mesopores with inherently nitrogen-doped. The electrochemical performance of the prepared activated carbon has been tested in various electrolytes such as KOH, NaOH, and Na2 SO4 . The activated carbon electrode shows a higher specific capacitance of 225 F/g at 1 A/g in NaOH electrolyte. Finally, the symmetric supercapacitor device is fabricated using prepared activated carbon and tested its electrochemical performances. The symmetric supercapacitor device delivered a cell capacitance of 81.7 F/g with energy and power densities of 11.23 Wh/kg and 248.8 W/kg, respectively with good rate capability (80.5 %) and capacitance retention (80 %) at higher current density. Graphical abstract: Unlabelled Image Highlights: Activated carbon prepared from bio-waste i.e., shrimp shell Activated carbon delivered a specific capacitance of 225 F/g at 1 A/g A specific energy density of 11.23 Wh/kg with cell capacitance of 81.7 F/g